2011
DOI: 10.1177/1362168811412026
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between listening development and strategy use

Abstract: This article reports on an investigation into the development of the listening proficiency and strategic behaviour of 15 lower-intermediate learners of French in England. We consider whether listeners remain in the same listening proficiency group after six months, and whether changes in strategy use are related to movement or non-movement between listening proficiency groups. We also examine whether learners’ strategic behaviour reflects their teachers’ approaches to listening. Data were gathered at two time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 15 publications
2
55
2
5
Order By: Relevance
“…Then, if they missed any of the activities, the instructor asks the learners to determine why they missed them and to discuss in small groups what strategies they could use to rectify their problems in future listening tasks. Examples of these strategies as outlined in several studies such as Chen (2009) and Graham, Santos, and Vanderplank (2011) include directed attention, selective attention, listening for gist, inferencing, and visualization.…”
Section: Evaluating Listening and Problem Solvingmentioning
confidence: 99%
“…Then, if they missed any of the activities, the instructor asks the learners to determine why they missed them and to discuss in small groups what strategies they could use to rectify their problems in future listening tasks. Examples of these strategies as outlined in several studies such as Chen (2009) and Graham, Santos, and Vanderplank (2011) include directed attention, selective attention, listening for gist, inferencing, and visualization.…”
Section: Evaluating Listening and Problem Solvingmentioning
confidence: 99%
“…Proponents of implicit learning have defended there is no need to teach explicitly second language (L2) learning strategies since students are able to consciously apply them for their own learning (Griffiths, 2004). However, recent research has shown that the explicit teaching of L2 learning strategies can be beneficial for language acquisition (Cohen & Macaro, 2007;Graham et al, 2011;Lyster & Saito, 2010), and, specifically, that "some types of strategies do appear to be more related to success in language learning than others" (Griffiths, 2013: 92).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, based on findings from questionnaires, class observations, and teacher interviews, language educators are often lacking in practical approaches, techniques and activities that they can apply in their classrooms (Graham, Santos, & Francis-Brophy, 2014;Graham, Santos, & Vanderplank, 2011). Further, teachers who turn to textbook teacher manuals for help may find little support for listening (Field, 2012).…”
Section: Introductionmentioning
confidence: 99%